2018
DOI: 10.3390/molecules23092332
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Determination of the Oil and Moisture Contents in Camellia gauchowensis Chang and Camellia semiserrata Chi Seeds Kernels by Near-infrared Reflectance Spectroscopy

Abstract: A fast and effective determination method of different species of vegetable seeds oil is vital in the plant oil industry. The near-infrared reflectance spectroscopy (NIRS) method was developed in this study to analyze the oil and moisture contents of Camellia gauchowensis Chang and C. semiserrata Chi seeds kernels. Calibration and validation models were established using principal component analysis (PCA) and partial least squares (PLS) regression methods. In the prediction models of NIRS, the levels of accura… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
8
2
Order By: Relevance
“…As a consequence of the investigation, absorbance spectra of Ethiopian mustard were obtained in the wavelength range of 400 to 2500 nm with a 2 nm interval. The mean raw spectral data (without pretreatment), treatment with invers MSC, and second-derivative of Ethiopian mustard samples were shown in and Perilla, 5,20 but, the spectrum of this study was different from the safflower spectrum reported by Elfadl et al 27 According the review, most of oilseed crops has comparable NIR spectra.…”
Section: Spectral Analysiscontrasting
confidence: 58%
See 1 more Smart Citation
“…As a consequence of the investigation, absorbance spectra of Ethiopian mustard were obtained in the wavelength range of 400 to 2500 nm with a 2 nm interval. The mean raw spectral data (without pretreatment), treatment with invers MSC, and second-derivative of Ethiopian mustard samples were shown in and Perilla, 5,20 but, the spectrum of this study was different from the safflower spectrum reported by Elfadl et al 27 According the review, most of oilseed crops has comparable NIR spectra.…”
Section: Spectral Analysiscontrasting
confidence: 58%
“…SEC and SEP were used to evaluate the predictive ability of the calibration and validation model. 20 The correlations between the SD of the wet chemical analyzed data and the prediction data by NIRS model (SECV or SEP) 10 were used to estimate the prediction ability of the model and calibrations, as well as the accuracy of the equations. 5 Equations with the highest R 2 , RPD, and 1-VR and the lowest SECV and SEP were considered the best models.…”
Section: Model Calibration and Validation For Near-infrared Spectroscopymentioning
confidence: 99%
“…Due to the strong combination of absorption bands for water at around 1450 nm (O-H), NIRS has been used for the estimation of the moisture content in grains and seeds [8]- [9]. In recent years, studies have shown that NIRS is a suitable method for quantifying trace amounts of the moisture content in Camellia gauchowensis Chang seed kernels [10]. The results shown that NIRS predicted accurately with a high coefficient of determination (R 2 =0.92) and a good standard error of prediction (SEP=0.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study demonstrated the ability to predict vitamin C and ellagic acid in whole and pureed Kakadu plum fruit samples using a handheld NIR spectrophotometer. In the next paper [8], the NIR spectroscopy method was developed to analyze the oil and moisture contents of the plant Camellia gauchowensis Chang and C. semiserrata Chi seeds kernels. The authors used principal component analysis (PCA) and partial least squares (PLS) regression methods for calibration and validation.…”
Section: Introductionmentioning
confidence: 99%